PERTUMBUHAN KAILAN (Brassica oleraceae) DENGAN PERLAKUAN MACAM MEDIA TANAM DAN PERBEDAAN VARIETAS PADA SISTEM HIDROPONIK DFT (Deep Flow Technique) - Yeni Yeni; Ratih Rahhutami; Betari Safitri; Priyadi Priyadi (Fakultas Pertanian, Universitas Janabadra, 2023)
Kailan is a leaf vegetable that has high nutrition and economic value and can be cultivated using DFT hydroponic system to support its productivity. The aims of this study to determine the influence of the types of growing media and differences in varieties and the interaction of the two on the growth in DFT hydroponic system. The study used a factorial complete randomized design consisting of the first factor wass the variety, namely Winsa variety (V1) and Full White variety (V2), the second factor was the type of growing media, namely rockwool (M1), sponge (M2), coco fiber (M3), and coco chip (M4). The results showed there was no interaction between the variety and the growing medium but there was a significant result of variety on the height parameters. The growing medium showed a significant result on the number of leaves, relative growth rate, net assimilation rate, root shoot ratio, and wet weight of kailan plants parameters. Cocochip media and Winsa varieties provide the best growth of kailan plants in all observation parameters.